2022
DOI: 10.1021/jacs.2c07150
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (+)-Aberrarone

Abstract: We disclose the first total synthesis of (+)-aberrarone, a diterpenoid natural product featuring a 5–5–5–6-fused tetracyclic skeleton. Key to the approach is a Au-catalyzed–Sn-mediated Meyer–Schuster–Nazarov–cyclopropanation–aldol cascade, which closes four rings in high yield. The convergent approach furnishes the natural product (+)-aberrarone stereoselectively in 15 steps. We highlight the benefits of using a Sn-alkoxide to considerably expand the opportunities of Au-catalysis for the synthesis of complex m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…Despite the drawbacks of trialkyl tin reagents, the limitations of all alternative methods still regularly force the use of tin-based deoxygenation protocols, from academic settings to large-scale industrial processes. [41][42][43][44][45][46][47] Overall, introduction of a general, nontoxic, and practical method to deoxygenate alcohols would enable broader implementation of alcohol deletion approaches in synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the drawbacks of trialkyl tin reagents, the limitations of all alternative methods still regularly force the use of tin-based deoxygenation protocols, from academic settings to large-scale industrial processes. [41][42][43][44][45][46][47] Overall, introduction of a general, nontoxic, and practical method to deoxygenate alcohols would enable broader implementation of alcohol deletion approaches in synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…While effective in some cases, these alternative methods suffer the synthetic limitations endemic to standard substitution chemistry; S N 1 requires readily ionizable alcohols and S N 2 proceeds only with unhindered alcohols. Despite the drawbacks of trialkyl tin reagents, the limitations of all alternative methods still regularly force the use of tin‐based deoxygenation protocols, from academic settings to large‐scale industrial processes [41–47] . Overall, introduction of a general, nontoxic, and practical method to deoxygenate alcohols would enable broader implementation of alcohol deletion approaches in synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several total syntheses of 3-6 have been reported . Previously, two synthetic studies of aberrarone were reported [30,31] and more recently, Carreira and co-workers reported [32] the first total synthesis of aberrarone through an impres-Scheme 1: Retrosynthetic analysis of aberrarone (1).…”
Section: Introductionmentioning
confidence: 99%
“…For example, several total syntheses of 3-6 have been reported. Previously, two synthetic studies of aberrarone were reported 29,30 and more recently, Carreira and co-workers reported 31 the first total synthesis of aberrarone through an impressive cascade reaction including gold-catalyzed Nazarov cyclization, cyclopropanation followed by intramolecular aldol reaction to forge the A, B and D rings. Impressed by the structural features and biological profiles, our group embarked a project on the total synthesis of this natural product.…”
Section: Introductionmentioning
confidence: 99%